Low Citrate Synthase Activity Is Associated with Glucose Intolerance and Lipotoxicity - Yosra Alhindi; Lobke M. Vaanholt; Mustafah Al-Tarrah; Stuart R. Gray; John R. Speakman; Catherine Hambly; Bader S. Alanazi; Brendan M. Gabriel; Arimantas Lionikas; Aivaras Ratkevicius (Journal of Nutrition and Metabolism)
Citrate synthase (CS) is a key mitochondrial enzyme. The aim of this study was to test the hypothesis that low CS activity impairs the metabolic health of mice fed a high fat diet (HFD) and promotes palmitate-induced lipotoxicity in muscle cells. C57BL/6J (B6) mice and congenic B6.A-(rs3676616-D10Utsw1)/KjnB6 (B6.A), a strain which carries the A/J allele of CS on the B6 strain background, were fed HFD (45% kcal from fat) for 12 weeks. C2C12 mouse muscle cells were used to investigate effects of CS knockdown on cell viability and signalling after incubation in 0.8 mM palmitate. CS activity, but not that of β-hydroxyacyl-coenzyme-A dehydrogenase was lower in the gastrocnemius muscle and heart of B6.A mice compared to B6 mice (P<0.001). During HFD feeding, glucose tolerance of mice decreased progressively and to a greater extent in B6.A females compared to B6 females, with males showing a similar trend. Body weight and fat gain did not differ between B6.A and B6 mice. After an 18 h incubation in 0.8 mM palmitate C2C12 muscle cells with ∼50% shRNA mediated reduction in CS activity showed lower (P<0.001) viability and increased (P<0.001) levels of cleaved caspase-3 compared to the scramble shRNA treated C2C12 cells. A/J strain variant of CS is associated with low enzyme activity and impaired metabolic health. This could be due to impaired lipid metabolism in muscle cells.